Pengaruh Penggunaan Media Audio Visual Dan Motivasi Belajar Terhadap Hasil Belajar IPA - Eko Wahyu, Deni; Hartono, Hartono; Suhari, Suhari (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the effect of using audio-visual media and learning motivation on student learning outcomes in science (IPA) in the subject of green plants, with a specific focus on the process of photosynthesis. Using a quantitative approach with a 2x2 factorial experimental design, this study involved 40 fifth-grade students from SDN Inpres Maidai, divided into two groups based on the type of learning media (audio-visual and images) and level of learning motivation (high and low). The instruments used included achievement tests and motivation questionnaires that had been validated for validity and reliability. The results of the two-way ANOVA analysis revealed that both learning media and learning motivation had a significant influence on student learning outcomes (p < 0.05), with audio-visual media and high motivation contributing the most to academic achievement. However, no significant interaction was found between the two variables, indicating that learning media and learning motivation operate independently in influencing learning outcomes. These findings emphasize the importance of selecting appropriate learning media and strategies to enhance learning motivation as two separate yet complementary approaches in improving the effectiveness of science education at the elementary school level.